Connecting Legal Education: Bridging the Gap from High School Civic Education toward Undergraduate Legal Studies - Ariesta Wibisono Anditya; Wina Driyan Pradana; Rizki Wahyuning Damayanti; Muhammad Ghoffar Ali; Eko Ramdani; Naufal El Qolbi N A; Levia Tri Mustika Dewi (Probono and Community Service Journal, 2023)
This community service project explores the vital role of Civics Education at SMA N 9 Yogyakarta in introducing students to legal concepts and general studies. Civics Education equips students with a fundamental understanding of law, citizenship, and democracy. The study employed a direct approach, revealing that Civics at SMA N 9 Yogyakarta significantly prepares students for their academic pursuits in law and general studies. This subject imparts a deep comprehension of essential legal principles, the rights and responsibilities of citizens, and democratic attitudes, guided by Civics teachers. The curriculum encompasses topics like the struggle for independence, constitutional matters, the political system, and human rights, fostering a sense of democracy, tolerance, and pluralism among students. Beyond academics, Civics hones vital social skills such as public speaking, debating, and collaboration, skills invaluable not only in legal courses but also in daily life and future careers. In summary, this community service emphasizes the critical role of Civics at SMA N 9 Yogyakarta as a strong foundation for students pursuing law and higher education.